Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1523/eneuro.0180-17.2017
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of Neuronal and Excitatory Network Properties between the Rat Brainstem Nuclei that Participate in Vertical and Horizontal Gaze Holding

Abstract: Visual Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 83 publications
1
4
0
Order By: Relevance
“…Therefore, the sustained activity responsible for horizontal and vertical eye position signals may be maintained by reciprocal loops in the PHN-VN and INC-VN networks, respectively (Evinger et al, 1977;Cannon and Robinson, 1987;McFarland and Fuchs, 1992;Sylvestre et al, 2003). Our present and previous studies demonstrated that sustained EPSC responses, indicating local excitatory networks, occurred in reduced preparations in which the connections to the VNs were discontinued (Saito and Yanagawa, 2010;Saito et al, 2017). These findings suggest that recurrent excitatory networks that produce sustained EPSC responses are deployed within the PHN and the INC.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…Therefore, the sustained activity responsible for horizontal and vertical eye position signals may be maintained by reciprocal loops in the PHN-VN and INC-VN networks, respectively (Evinger et al, 1977;Cannon and Robinson, 1987;McFarland and Fuchs, 1992;Sylvestre et al, 2003). Our present and previous studies demonstrated that sustained EPSC responses, indicating local excitatory networks, occurred in reduced preparations in which the connections to the VNs were discontinued (Saito and Yanagawa, 2010;Saito et al, 2017). These findings suggest that recurrent excitatory networks that produce sustained EPSC responses are deployed within the PHN and the INC.…”
Section: Discussionsupporting
confidence: 64%
“…All experimental procedures were approved by the Animal Care Committee of Nara Medical University, and the experiments were conducted in accordance with the guidelines outlined by the US National Institutes of Health regarding the care and use of animals for experimental research. Although our previous studies were performed in slice preparations obtained from Wistar rats (Saito and Yanagawa, 2010;Saito et al, 2017), we used slices obtained from Long-Evans rats of either sex in this study because pigmented rats have higher visual acuity than albino rats (Birch and Jacobs, 1979;Prusky et al, 2002). A total of 30 Long-Evans rats (18 -21 postnatal days old) were used in this study.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The analysis of the relationship between the firing rate before ATP application and the effects of ATP on the firing rate revealed that the firing rate of neurons that exhibited a decrease to zero was significantly smaller than the firing rate of neurons that exhibited an increase or decrease (Figure c2). Although we did not identify the neuronal types in this study, PHN neurons that exhibit a firing pattern with few spikes during the 400‐ms current injection show a low spontaneous firing rate (Saito, Sugimura, & Yanagawa, ; Saito et al., ; Shino, Ozawa, Furuya, & Saito, ; Shino et al., ; Zhang et al., ). Therefore, ATP may completely inhibit the firing of this type of PHN neuron.…”
Section: Discussionmentioning
confidence: 97%